Full-stack web development for auto-assessment platform - Chua, Chong Yih (Nanyang Technological University, 2023)
The field of Computer Science education has witnessed a surge in the number of students seeking to understand its intricate concepts. As the demand for quality education grows, the need for efficient evaluation tools becomes increasingly evident. While automated assessment platforms have proved invaluable in evaluating programming skills, they fall short when it comes to assessing Hardware Description Languages (HDLs). HDLs are specialized languages used to simulate digital circuits and systems, posing unique challenges that current assessment tools designed for General-Purpose Programming Languages (GPLs) cannot address.